Analysis of Educational Game Development Needs for Improvement Students' Critical Thinking Ability in Informatics Subjects - Samin; Gunarhadi; Efendi, Agus (Future Science, 2021)
Critical thinking skills are needed in the learning process, especially in learning Informatics. The use of technology in learning can be done by using learning media in the form of educational games that are integrated in learning. The purposes of this study are 1) to determine the perception of educational games, 2) to obtain information on the need for formats, criteria, content of educational games, 3) the role of developing educational games for improving critical thinking skills. The method used in this research is a survey to find out the initial data which is the process of developing educational game products. The instrument used is a questionnaire sheet. The data analysis technique that will be used is quantitative and qualitative descriptive statistical analysis techniques. The schools that were used as research samples were 22 SMP/MTs spread across Karanganyar Regency, Boyolali Regency, and Surakarta City. Each school selected 1 teacher of Informatics Subject and 3 students. The results showed that teachers and students had good perceptions of Informatics educational games. According to the teacher, the need for educational games is games containing evaluation and simulation questions, while adventure-type games are needed by students. The educational game content required includes learning materials, evaluation questions, adventure games, quiz games, simulations. Educational game format needed that is challenging and interesting. Informatics educational game criteria include attractive and interactive design, sufficient duration, usability, easy access, user friendly interface, appropriateness, relevance. Teachers and students believe that educational games can play a role in improving students' critical thinking skills.